Chemical composition of oil palm frond / Farhana Jasmi, Farahin Yusoff and Jamaludin Kasim - Jasmi, Farhana; Yusoff, Farahin; Kasim, Jamaludin (2011)
The growth of oil palm plantation has created the massive amounts of biomass especially oil palm frond. This issue will give negative influence on the environment and replanting operations. The higher amount of biomass gives an idea of the possibility to produce panel product or wood composite product and therefore reduce the dependency of wood based industry on solid wood. The objective of this study was to determine the chemical composition of oil palm frond. The findings in this study will provide advanced understandings on its chemical composition and the suitability in panel product production. The chemical analyses observed were lignin, ash, holocellulose, alcohol solubility, alkali solubility, and hot and cold water solubility. The results are 23.86%, 3.41%, 75.65%, 5.68%, 33.52%, 12.5% and 10.23% respectively. This study was conducted according to TAPPl standard and Wise et at. The chemical composition of OPF indicates that OPF is suitable in production of panel product